Faktor-faktor yang mempengaruhi Tax Avoidance dengan nilai perusahaan sebagai variabel mediasi - Dhinata, Monica; Jessica, Jessica; Dewi Fortuna, Putri; Allysya, Stefhanie (ARKA INSTITUTE, 2023)
Tax avoidance is an effort by companies to minimize the tax burden that will be paid by taking advantage of existing loopholes in taxation. The objective of this study is to examine and analyze the factors that can influence tax avoidance with firm value as a mediating variable. This research aims at LQ45 issuers listed on the Indonesia Stock Exchange during the 2019-2021 period. This type of research is quantitative research. The population in this study amounted to 60 companies. The sampling method used was purposive sampling method and a sample of 34 companies was obtained with a total of 102 observations. The data analysis method used was multiple linear regression analysis and was processed using IBM SPSS AMOS 24 software. The results showed that partially ROA and DER did not have an effect on tax avoidance, company size has a negative effect on tax avoidance, and firm value as a mediating variable cannot mediate the relationship between ROA, DER, and firm size and tax avoidance. It can be concluded that ROA, DER, and company size are not factors that influence Tax Avoidance.